Analysis of total factor productivity changes in Islamic and conventional banks: empirical evidence from three regions - W. Jubilee, Ribed Vianneca; Kamarudin, Fakarudin; Hussain, Hafezali Iqbal; Abdul Latif, Ahmed Razman; Zainal, Nurazilah
The objective of this study is to examine total factor productivity changes (TFPCH) in Islamic and conventional banks to determine whether they exhibit progression or regression. As earlier studies have focused mainly on productivity in conventional banks rather than Islamic banks, the current study aims to bridge the gap in the literature by investigating both types of bank in the Middle East, Southeast Asia, and South Asia. A total of 385 Islamic and conventional banks from 18 countries were selected, with data acquired for the period from 2008 to 2017. Panel data analysis was undertaken using DEA-based MPI to investigate the impact of selected determinants of banks’ productivity, as indicated by TFPCH. The results from both the t-test and nonparametric tests revealed that Islamic banks are more productive than conventional banks, which can be attributed to the increase in efficiency changes. However, no statistically significant difference in productivity exists between the types of bank. The main contribution of this study is that it provides not only corroboration for previous studies but also additional insight into bank productivity in Islamic and conventional banks, which will be important to banks, regulators, investors, and researchers.